On the Line Business Education in the Digital Age (Springer International Publishing, 2018)
This book presents different perspectives of online business education - how it is designed, delivered and how it supports advances in management disciplines. The authors describe online platforms in their provision of timely, excellent and relevant business education. The book starts by examining the emergence of online business education. It offers insights for use to business educators in design and implementation of online learning. It presents and discusses technologies for class facilitation and collaboration including tools used to bring content and issues to life. Disruptive approaches and new directions in online business education are examined. The book is ideal for business educators, administrators, as well as business practitioners that have an interest in delivering high quality business education using online platforms and tools. On the Line: Business Education in the Digital Age is divided into three sections. Section 1 presents papers on "why" business education is viable and sustainable in today's context. Treating education as a service, this section describes new techniques for creating a better online business education experience. It also looks at the role advanced data analytics can play in enhancing the quality of online business education. Section 2 delves into "how" online business education works. It presents conceptual models for teaching in specific disciplines, learning design that describes what business educators do and how programs work. This section also addresses performance assessments and quality assurance measures that help to demonstrate the efficacy of online pedagogy. Practical applied papers are used in this section to highlight the use of learning platforms, tools and their application specific to businesses that build knowledge and skills and make students 'work ready'. Finally Section 3 of the book addresses the "so what?" or the outcomes and impacts of online business education. This section targets where business education needs to take learning next, for example to support sustainable business, ethical decision making and inclusive and collaborative leadership. Chapters deal with topics such as how distributed online environments may work better to support knowledge and soft skill building directly relevant for organizations today. Other learning outcomes showing the value of online business education are discussed. Academics, alumni and consultants from over fifteen institutions and organizations around the world contributed to this book.